SELF ASSESSMENT IMPROVEMENT STRATEGIES (TAXPAYER COMPLIANCE, TAXPAYER INSPECTION, AND TAX MORALE APPROACH) - Misra Herlambang (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2021)
Self-assessment system approach is a system in which taxpayers are given the authority to report their own income to the tax service office. The purpose of this research is to explore the implementation and strategies to support in improving the self-assessment system in KPP Pratama Kendari City. This study describes taxpayer compliance, tax audit, and self-assessment system strategies through the tax morale approach. The results of this study indicate that the implementation of taxpayer compliance still needs to be improved, tax audits have been carried out optimally, and tax morale raises three topics, namely trust in government, trust in court and legal systems, and trust in tax officials.